Sleep Disturbances and Concentration in Elementary School Students - Yulianti, Natalia Ratna; Puspita, Angela Dyah Alfena; Wahyuningrum, Eka (Sahabat Publikasi Kuu, 2025)
Introduction: Sleep disturbances affect concentration, leading to a decline in students' focus. This decrease in concentration results in lower-quality student activities. Students become less attentive during learning, which causes them to feel lazy and decreases their motivation to study, ultimately lowering their academic performance. The decline in academic achievement can make students feel left behind compared to their peers, leading to anxiety and stress. Previous studies have shown varying results regarding the relationship between sleep disturbances and student concentration. Therefore, this study aims to examine the relationship between sleep disturbances and concentration among students at SD Negeri Wonotingal, Indonesia. Methods: This study is an analytical observational quantitative study using a cross-sectional approach. The sample was taken using proportionate stratified random sampling, resulting in 136 respondents. Data were collected using the Sleep Disturbance Scale for Children (SDSC) to assess sleep disturbances and the Grid Concentration Test (GCT) to measure concentration levels. The data were analyzed using the Kolmogorov-Smirnov statistical test. Results: The results of the study showed a p-value of 0.037. Since the p-value is less than 0.05, H0 is rejected and H1 is accepted, meaning there is a significant relationship between sleep disturbances and students' concentration at SD Negeri Wonotingal, Indonesia. Conclusion There is a significant relationship between sleep disturbances and students' concentration at SD Negeri Wonotingal, Indonesia. Future research is expected to involve larger and more diverse samples and to examine other factors that may influence the relationship between sleep disturbances and concentration